Implementasi Metode TOPSIS dalam Penentuan Sanksi Pelanggaran Siswa di Sekolah - Umi Khultsum; Ghofar Taufik (STMIK Budi Darma, 2023)
Technology has a tremendous impact on education in terms of obtaining information for both teachers and students in the form of technological system assistance for calculating and analyzing the information obtained as well as student performance reports in computerized form and easily accessible for supervision. This decision support system for determining student violation sanctions is implemented in order to overcome possible problems that occur if there are errors in the form of errors in calculating student violation points which are done manually. This research aims to support the school's decision and help determine appropriate sanctions for students who commit violations. The website-based decision support system that will be developed in this research uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. In implementing the system creation, a software development method was used, namely the waterfall method. The results of manual calculations and calculations carried out by the decision support system that had been created obtained the same results, namely Erlangga Kurniawan (A5) with a preference value of 0.8371256, Erika Kusumawati (A6) with a preference value of 0.16521256, Dani Syahputra (A3) with a preference value of 0.10663703, Wawan Hidayat (A9) with a preference value of 0.10091779, and Andika Putra (A1) with a preference value of 0.06921825 received heavy sanctions. The Decision Support System using the TOPSIS Method can help schools to determine which students will receive heavy sanctions and light sanctions effectively and efficiently.